Transcriptional Suppression of miR-181c by Hepatitis C Virus Enhances Homeobox A1 Expression - Mukherjee, Anupam (American Society for Microbiology, 2014)
Hepatitis C virus (HCV)-induced chronic liver disease is one of the leading causes of hepatocellular carcinoma (HCC). The molecular events leading to HCC following chronic HCV infection remain poorly defined. MicroRNAs (miRNAs) have been implicated in the control of many biological processes, and their deregulation is associated with different viral infections. In this study, we observed that HCV infection of hepatocytes transcriptionally downregulates miR-181c expression by modulating CCAAT/enhancer binding protein β (C/EBP-β). Reduced expression of the pri-miR-181c transcript was noted following HCV infection. In silico prediction suggests that homeobox A1 (HOXA1) is a direct target of miR-181c. HOXA1 is a member of the homeodomain-containing transcription factor family and possesses pivotal roles in normal growth, development, and differentiation of mammalian tissues. Our results demonstrated that HOXA1 expression is enhanced in HCV-infected hepatocytes. Exogenous expression of the miR-181c mimic inhibits HOXA1 and its downstream molecules STAT3 and STAT5, which are involved in cell growth regulation. Interestingly, overexpression of miR-181c inhibited HCV replication by direct binding with E1 and NS5A sequences. Furthermore, accumulation of HCV genotype 2a RNA with miR-181c was observed in an RNA-induced silencing complex in Huh7.5 cells. Our results provide new mechanistic insights into the role of miR-181c in HCV-hepatocyte interactions, and miR-181c may act as a target for therapeutic intervention. IMPORTANCE Chronic HCV infection is one of the major causes of end-stage liver disease, including hepatocellular carcinoma. An understanding of the molecular mechanisms of HCV-mediated hepatocyte growth promotion is necessary for therapeutic intervention against HCC. In this study, we have provided evidence of HCV-mediated transcriptional downregulation of miR-181c. HCV-infected liver biopsy specimens also displayed lower expression levels of miR-181c. We have further demonstrated that inhibition of miR-181c upregulates homeobox A1 (HOXA1), which is important for hepatocyte growth promotion. Exogenous expression of miR-181c inhibited HCV replication by directly binding with HCV E1 and NS5A sequences. Taken together, our results provided new mechanistic insights for an understanding of the role of miR-181c in HCV-hepatocyte interactions and revealed miR-181c as a potential target for therapeutic intervention.